FEMINISMS, CHURCHES, AND WOMEN S SPIRITUALITIES - Parker-Gumucio, C (UNIV ARTURO PRAT, INST ESTUDIOS INDIGENAS, 2025)
The article analyzes the complex interactions between feminist movements, religious institutions, and women s spiritualities in Latin America. Through a critical review of the region s sociocultural and religious context, it highlights how feminist struggles have challenged patriarchal structures, including those deeply rooted in churches. Although studies on gender and diversity have proliferated, the author emphasizes that forms of male domination still persist, hindering gender equity. The text explores the tension between church criticisms of so-called "gender ideology" and feminist movements. Beyond this conflict, it underscores the emergence of female spiritualities created by women, which reconfigure their role in the religious sphere. These spiritualities-often outside traditional ecclesiastical frameworks-represent forms of resistance and re-signification by women distanced from power, yet not from the religious. From the feminine in popular religiosities and feminist theology networks to women s spirituality circles, the article proposes understanding these practices as new expressions of agency and cultural transformation. This rethinks both the role of religion and spirituality in contemporary feminist struggles. In sum, the article invites a reconsideration of the dynamics between gender, faith, and society, highlighting the richness and complexity of emerging female spiritualities in Latin America.